Evaluation of bacterial and fungal contamination of kitchens of Birjand University of Medical Sciences - Seyyedeh Masoomeh Rahimi; Maryam Ebrahimi; Behnam Barikbin; Tayebeh Zeinali (BMC Research Notes, 2019)
Abstract Objective This study aims to evaluate the total bacterial and fungal count of tools, devices and surfaces of kitchens of the centers affiliated to Birjand University of Medical Sciences. In this study, 200 samples from four kitchens of Birjand University of Medical Sciences were obtained. After the preparation of serial dilutions, samples were cultured in plate count agar (PCA) plates and Sabouraud dextrose agar (SDA). After incubation at 37 and 25 °C for 24–48 and 72–96 h respectively, the microbial and fungal colonies were counted. Results The mean bacterial and fungal count of kitchens was 7.7 * 107 and 7.6 * 104, respectively. The highest and lowest levels of bacterial contamination were related to tools/devices and cover of tools/work clothes and the highest and lowest levels of fungal count were related to forks and spoons and the tools and devices of the storage site. The rate of contamination in the kitchens of Birjand University of Medical Sciences was relatively high. Thus, serious, continuous and accurate monitoring of the units, training of people working in all stages of cooking and disinfection the tools and devices are essential for control and prevention of disease transmission.